Relationships among white-tailed deer density, harvest, and landscape metrics in TN, USA - Heidi L. Adams; Robert E. Kissell; Daryl Ratajczak; Edward L. Warr; Roger D. Applegate; Lynn Barrett; Tabitha Lavacot; David Graves (European Journal of Wildlife Research, 2020)
Landscape and harvest indices are frequently used to represent white-tailed deer ( Odocoileus virginianus ) density. However, the relationship between deer density and specific landscape indices is unclear. Harvest is another metric often used to estimate deer density. Our objective was to model the relationship among deer density, landscape metrics, and harvest density of deer in TN, USA. We estimated deer density across 11 regions in 2011 using distance sampling techniques. We developed 18 a priori models to assess relationships among deer density, harvest density, and landscape metrics. Estimates of deer density ranged from 1.85 to 19.99 deer/km 2 . Deer density was best predicted by harvest density and harvest density + percent woody area. However, harvest density was the only important variable in predicting deer density (Σω i = 0.700). Results of this study emphasize the significance of harvest density in deer management. While the importance of harvest as a management tool for deer is likely to increase as landscapes are fragmented and urbanized, specific management guidelines should be based upon deer densities and landscape metrics when they are important.

The collapse of cycles in the dynamics of North American grouse populations - Christopher K. Williams; Anthony R. Ives; Roger D. Applegate; Jörgen Ripa (Ecology Letters, 2004)
Cyclic dynamics of bird and mammal populations are commonly reported in northern latitudes throughout the world, and recent European observations on rodents and grouse suggest that cycle periods decline towards southern latitudes. To investigate latitudinal patterns of cyclic dynamics in North America, we assembled 27 long‐term data sets collected between 1939 and 2001 for three grouse species. By fitting the data with autoregressive models to measure direct and delayed density dependence, we show that, in contrast to European studies, North American grouse exhibit period increases from north to south, with cycles collapsing via period lengthening. This occurs because delayed density dependence decreases in southern latitudes, whereas direct density dependence increases. These results show that cyclic dynamics can dissipate by period lengthening as well as the period shortening postulated for European grouse and rodents.

Compensation Issues in Natural Resource Professions - ROGER D. APPLEGATE (Conservation Biology, 2003)